Embedding Mathematics in Socio-Scientific Games: The Mathematical in Grappling with Wicked Problems - Chronis Kynigos (MDPI AG, 2024)
This paper discusses the ways in which digitally enabled transformation in mathematics education could envisage a role for rationality in post-normal science and wicked problems. The scene is set firstly by reviewing the ways in which digital media have been designed and used in transformative mathematics education as a rationale for thinking about such media for wicked problem education. The problem is set in epistemological terms: can normal science approaches contribute to post-normal science? By considering the basic arguments regarding wicked problem education, I focus on the discussion of a specific constructionist digital tool called 'ChoiCo: Choices with Consequences', designed to embed mathematical ideas and facilitate mathematical reasoning, yet be about grappling with wicked problems. The final section discusses student discourse to set the scene for what such reasoning might look like in the context of grappling with wicked problems.